Total chemical synthesis of methylated analogues of histone 3 revealed KDM4D as a potential regulator of H3K79me3. Issue 18 (15th September 2017) - Jbara, Muhammad; Guttmann-Raviv, Noga; Maity, Suman Kumar; Ayoub, Nabieh; Brik, Ashraf
Graphical abstract: Abstract: Histone H3 methylation plays an important role in regulating gene expression. In histones in general, this mark is dynamically regulated via various demethylases, which found to control cell fate decisions as well as linked to several diseases, including neurological and cancer. Despite major progress in studying methylation mark at various positions in H3 histone proteins, less is known about the regulation of methylated H3 at Lys79. Methylation at this site is known to have direct cross-talk with monoubiquitination of histone H2B at positions Lys120 and 34, as well as with acetylated H3 at Lys9. Herein we applied convergent total chemical protein synthesis to prepare trimethylated H3 at Lys79 to perform initial studies related to the regulation of this mark. Our study enabled us to identify KDM4D lysine demethylase as a potential regulator for trimethylated H3 at Lys79.